cardiovascular Medicine - eric j topol, Robert M. Califf MD (Lippincott Williams & Wilkins, 2007)
The field of cardiovascular medicine has gone through some radical changes since the last edition. These include the use of multidetector CT angiography to eventually replace diagnostic cardiac catheterization, the routine use of drug-eluting stents for percutaneous coronary intervention, the use of pulmonary vein isolation procedures to ablate atrial fibrillation, the more wide scale acceptance of statins, ACE inhibitors and defibrillators, and resynchronization therapy for the treatment of heart failure. We are right at the cusp of breakthroughs in the genomics of complex cardiovascular traits, such as myocardial infarction and valvular heart disease, and for this reason the molecular cardiovascular content has been emphasized. All of these marked changes in the field have been highlighted in this edition. There are new chapters covering women and heart disease, prevention of heart failure, stem cells and myocardial regeneration, cardiac resynchronization, peri-operative management, percutaneous valve repair and intracardiac procedures as well as several others that capture the advances in molecular cardiology.